Role of ion-pair interactions on asphaltene stabilization by alkylbenzenesulfonic acids - Goual, Lamia; Sedghi, Mohammad (Journal of colloid and interface science, 2015)
[Display omitted] •Asphaltene interactions with DBSA and alkylphenols are different.•Flocculates with DBSA consist of thick filaments with short lateral ramifications.•DBSA promoted the formation of large and compact flocculates.•Flocculation mechanism driven by ion-pair interactions was proposed. The dispersion of asphaltenes by dodecylbenzenesulfonic acid (DBSA) has been the subject of several studies in the past. However, it is unclear how these interactions affect the structure of asphaltenes and why asphaltene aggregates are larger in the presence of ionic DBSA. The main goal of this study was to address these points using a combination of high-resolution transmission electron microscopy (HRTEM) and molecular dynamics (MD) simulations. Another objective was to compare ionic DBSA (i.e., dodecylbenzenesulfonate or DBS−) to nonionic amphiphiles such as alkylphenols. A striking similarity between dodecylbenzenesulfonate and alkylphenols was that both favored the formation of filamentary rather than globular asphaltene flocculates. However the mechanism by which those filaments formed was very different. Two strong electrostatic interactions between DBSA and asphaltenes were found: (i) those between protonated asphaltenes (i.e., AH+) and DBS− molecules, which were fifteen times stronger than asphaltene–alkylphenol interactions, and (ii) those between two asphaltene–dispersant pairs (i.e., AH+–DBS− ion pairs), which did not exist with alkylphenols. These interactions promoted the formation of large and compact asphaltene flocculates, as compared to small and loose ones formed without DBSA. Flocculates with DBSA could further bind to each other through ion-pair interactions. The binding occurred in series (generating long filaments) or in parallel (generating lateral ramifications). However the series configuration was energetically favored due to less steric effects generated by the side aliphatic chains of asphaltenes and DBSA.